The relationship between mental health dimensions and academic achievement among students of the College of Education at Princess Nourah University at the Kingdom of Saudi Arabia - Alwail, Amal Omar (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the relationship between mental health dimensions and academic achievement among students of the College of Education at Princess Nourah University in the Kingdom of Saudi Arabia, to achieve the objectives of the study, the researcher used the descriptive-analytical approach, and the mental health scale by Al-Quraiti & Al-Shakhs (1998) was used as the tool of the study, the scale was applied to (201) female students from the College of Education at Princess Nourah University. The study reached many results, the most prominent of which were: the presence of a moderate level of mental health among the study sample of university students, where the average was (64.54), also, the results revealed that there are statistically significant differences at the level of (0.05) between the average scores of the study sample in the two dimensions (sense of competence and self-confidence, emotional maturity and the ability to self-control), as well as in the total score of the mental health scale according to the difference of specialization (psychology, kindergarten) was for the benefit of female students of the department of psychology. Based on the results of the study, the researcher proposed a number of recommendations, the most prominent of which were: studying the role of academic achievement in influencing individuals’ mental health, and studying the principles and practices necessary to improve the mental health of individuals and protect them from mental disorders.